MEED Middle East Economic Digest - Broustail, Joel (2013)
In the article, the author discusses the six main strategic motivations, as well as the six major development strategies in order to ensure business growth. Among the strategic motivations are to keep pace with an expanding market, to change the rules of the game through radical innovation, and to consolidate. The development strategies include internal growth, alliance with a rival, and acquisition